2014
DOI: 10.1186/1472-6939-15-81
|View full text |Cite
|
Sign up to set email alerts
|

Public’s attitudes on participation in a biobank for research: an Italian survey

Abstract: BackgroundThe creation of biobanks depends upon people’s willingness to donate their samples for research purposes and to agree to sample storage. Moreover, biobanks are a public good that requires active participation by all interested stakeholders at every stage of development. Therefore, knowing public’s attitudes towards participation in a biobank and biobank management is important and deserves investigation.MethodA survey was conducted among family members of patients attending the outpatient department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
83
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 20 publications
13
83
2
4
Order By: Relevance
“…Similar to other studies [12][13][14], this study revealed a low rate of knowledge on the practice of genetic database banking (17%), of whom the majority were of higher level of education. However, supportive public opinion on acceptance of gene banking, participation in genetic research and setting protection laws among the aware and the unaware groups after being introduced to the subject, achieved good results, also similar to the findings in Refs.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to other studies [12][13][14], this study revealed a low rate of knowledge on the practice of genetic database banking (17%), of whom the majority were of higher level of education. However, supportive public opinion on acceptance of gene banking, participation in genetic research and setting protection laws among the aware and the unaware groups after being introduced to the subject, achieved good results, also similar to the findings in Refs.…”
Section: Discussionsupporting
confidence: 86%
“…However, supportive public opinion on acceptance of gene banking, participation in genetic research and setting protection laws among the aware and the unaware groups after being introduced to the subject, achieved good results, also similar to the findings in Refs. [12][13][14]. So far, as public acceptance is concerned, the educated scored better than the uneducated in both aware and unaware groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Empirical studies show that Europeans are very willing to participate in biobank research, mostly for altruistic reasons. 29,30 However, contextual factors, such as people's general trust in political and other institutions, impact perceptions of biobank research. 31 People in the Nordic welfare states, for example, regard participating in research as their civic duty, a contribution to the common good.…”
Section: Ethical Framework For Participation In Biobank Researchmentioning
confidence: 99%
“…Structuring ethics and consent standards: Systematic qualitative study of the opinions to cancer biobanking performed at public and private hospitals in NSW demonstrated that informed consent for general use of biospecimens for future unspecified research was given willingly by the majority of patients and parents of children and was supported by lay persons. 53,54 Worldwide, reports regarding informed consent for the collection of tissues for future unspecified research by biobanks 55,56 indicate that willingness to consent was independent of all factors including age, sex, and tumor type. Yet, debates about the consents, its scope (broad or specific), the merits of opt-in and opt-out consenting, and content of consent requests have not been resolved.…”
mentioning
confidence: 99%